2012
DOI: 10.1093/jac/dks456
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of aminocoumarins and fluoroquinolones on the SOS response and adaptability in Staphylococcus aureus

Abstract: In summary, aminocoumarins inhibit recA expression in S. aureus and probably delay the process of developing antibiotic resistance and gene transfer. A clinical re-evaluation of these compounds as well as designing more applicable derivatives should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 61 publications
0
63
2
2
Order By: Relevance
“…Examples of suppressors of the SOS response induced by fluoroquinolones were reported in Gram-positive and Gram-negative bacteria, such as the polyphenols baicalein (24), curcumin (25), and suramin (polysulphonated naphthylurea) (26), which have the ability to disassemble RecA single-stranded DNA filaments. Novobiocin blocks the ATP-binding site of the GyrB and inhibits ciprofloxacin and UV-induced SOS response (27,28). The small-molecule N6-(1-naphthyl)-ADP acts as an ATP competitor, which prevents the formation of the RecA-DNA filament that is essential for all RecAassociated functions (29).…”
mentioning
confidence: 99%
“…Examples of suppressors of the SOS response induced by fluoroquinolones were reported in Gram-positive and Gram-negative bacteria, such as the polyphenols baicalein (24), curcumin (25), and suramin (polysulphonated naphthylurea) (26), which have the ability to disassemble RecA single-stranded DNA filaments. Novobiocin blocks the ATP-binding site of the GyrB and inhibits ciprofloxacin and UV-induced SOS response (27,28). The small-molecule N6-(1-naphthyl)-ADP acts as an ATP competitor, which prevents the formation of the RecA-DNA filament that is essential for all RecAassociated functions (29).…”
mentioning
confidence: 99%
“…18 Cellular processes acting upon the ternary complexes have been hypothesized to be responsible for the double-stranded DNA breakage that occurs, along with the rapid induction of the SOS response. 19,20 It has been suggested that the rapid inhibition of DNA synthesis is specifically associated with gyrase molecules located at the replication fork. 21 Early studies of the addition of nalidixic acid to E. coli showed no inhibition of RNA synthesis for ~2 h along with continued increase in cell mass, consistent with the microscopic observation of cell filamentation.…”
Section: Discussionmentioning
confidence: 99%
“…Novobiocin, the structurally related chlorobiocin as well as coumermycin A1 are 3-amino-4,7-dihydroxycoumarin derivatives, alternatively referred to as the classical aminocoumarin antibiotics. Classical aminocoumarins act as competitive inhibitors of bacterial topoisomerase, more precisely DNA gyrase [5,6]. Competitive inhibition of DNA gyrase by the classical aminocoumarin antibiotics results from an overlap in binding sites between the sugar moiety of the aminocoumarins (Figure 1, numbered in blue) and the adenine ring of ATP which is required for the gyrase activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, differences in the binding sites between the fluoroquinolone antibiotics (e.g. moxifloxacin which primarily inhibits topoisomerase IV but also interacts with gyrase) allow fluoroquinolone antibiotics to maintain potency in aminocoumarin resistant bacteria and vice versa [5,6,11]. Mycobacterial gyrase, which is a validated drug target in Mycobacterium tuberculosis, is also the likely target for the fluoroquinolone class antibiotics as M. tuberculosis does not express the topoisomerase IV enzyme [12].…”
Section: Introductionmentioning
confidence: 99%